35th Joint Propulsion Conference and Exhibit 1999
DOI: 10.2514/6.1999-2810
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic damping predictions for turbomachine blade rows using a three-dimensional time marching simulation

Abstract: Flow induced vibration of turbomachine blade rows is a coupled fluid-structure problem. Thus, rather than separate fluid and structural models, a coupled interacting fluid-structures analysis is needed. This research addresses this need by extending the finite element code ALE3D that solves the three-dimensional Euler equations to model the unsteady aerodynamics of turbomachine blade rows. The same finite element model is applied to both the blading and the fluid, resulting in consistency between the fluid and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…A similar method for estimating the damping of a turbomachinery blade undergoing multiple vibration modes was reported in Gottfried and Fleeter. 12 Using the above correlations, the decoupled approach estimated an averaged aerodynamic damping coefficient of 0.006. from the unsteady pressure signals.…”
Section: Fluid-structure Interaction (Fsi) and Modelling Approachmentioning
confidence: 99%
“…A similar method for estimating the damping of a turbomachinery blade undergoing multiple vibration modes was reported in Gottfried and Fleeter. 12 Using the above correlations, the decoupled approach estimated an averaged aerodynamic damping coefficient of 0.006. from the unsteady pressure signals.…”
Section: Fluid-structure Interaction (Fsi) and Modelling Approachmentioning
confidence: 99%
“…The blade response in the flow case is due mainly to the influence of hourglass viscosity and that from the unsteady pressure. A similar method for estimating the damping of a turbomachinery blade undergoing multiple vibration modes in a time domain simulation of a fluid-structure interaction analysis was presented in Gottfried and Fleeter [9]. In using the above method, an estimated value of 5 Ubulom GTP-20-1395 the aerodynamic damping was obtained from the pressure field history on the blade surface.…”
Section: ) Fluid-structure Interaction Modellingmentioning
confidence: 99%
“…Li and He [19] studied the aerodynamic damping of transonic fan, which pointed out that the aerodynamic damping could be considered to be linear under small oscillating amplitude. During the research on flutter and forced response of turbomachinery bladings, Gottfried and Fleeter [20] and Moffatt and He [21] concluded that blade vibration amplitude was less than 1 per cent of the blade chord, in which range the flow and unsteady aerodynamic force was linear well; thus, the non-linear influence could be ignored. The damping matrix diagonalization is realized by some engineering approximate approaches.…”
Section: Numerical Methodologymentioning
confidence: 99%